Turtles and tortoises of Syria: Diversity, distribution, and conservation - Aidek, Ahmad E.; Saad, Adib; Jablonski, Daniel; Esterbauer, Hans; Fritz, Uwe (Zootaxa, 2024)
Syria is home to a wide range of ecosystems and landscapes that support a variety of animal species, including reptiles. Currently, Syria hosts nine species of chelonians (turtles and tortoises) from six different families, making its family-level diversity remarkable for the Mediterranean and the Middle East. We conducted a comprehensive review of existing literature, database information, and museum records, and incorporated new field data collected between 2019 and 2023 to document the distribution and conservation status of chelonians in Syria. As a result, we present an updated species list, accompanied by relevant information and occurrence maps for each turtle and tortoise species found in the country. Our investigation has yielded a total of 321 distribution records for Syrian chelonians (including nests of marine species), 105 of which are new. In addition, we verified 18 sites previously documented in the literature. Among the most frequently recorded species is Testudo graeca terrestris Forskål, 1775. In addition, for the first time, we have systematically evaluated the records of two marine turtle species that use Syrian coasts as nesting sites. This study is the most comprehensive and up-to-date source of information on the distribution and biogeography of chelonians in Syria, encompassing both historical and current geographic records. In addition, our data provide a zoogeographic overview and a substantial dataset of distribution information that can be used for subsequent analysis of macroecological patterns, distribution patterns, and conservation efforts related to this group of reptiles.